Z- Plasty: an Effective Technique for Pilonidal Sinus - Khan, Mohammad Rabiul Karim; Begum, Most Nurunnahar; Islam, Sharmin; Islam, Abu Faisal Md Ariful; Ahmed, Rafiq Uddin; Khan, Mohammad Hedayet Ali (Journal of Dhaka Medical College, 2021)
Introduction: Pilonidal sinus is a commonly encountered problem with multiple surgical options. With Z- plasty, primary closure ensues faster healing while the alteration of local anatomy reduces recurrence. The extremely low recurrence rate following Z-plasty for pilonidal sinus results from the fact that the operation was planned with the true physiology of the disease in mind. It is the deep natal cleft which predisposes to pilonidal sinuses and this architecture is altered with multiple Z -plasty. Materials and methods: A prospective, observational study was conducted into department of Plastic Surgery and burn, Dhaka Medical College and Hospital. Here 18 patients with pilonidal sinus were treated by Z – plasty between 2013 to 2018. Result: There was only one recurrence during the follow up time. There were no necrosis of flaps and no wound dehiscence. Conclusion: The Z-plasty technique is an effective procedure for treating pilonidal sinus in terms of both faster healing and lower recurrence rate. J Dhaka Medical College, Vol. 28, No.2, October, 2019, Page 164-171